Sociological and Educational Perspectives on Cross-Platform Micro Drama Adoption in the Digital Era - Chen, Yilin; Tang, Qi; Liu, Zhonghao (European Journal of Social Science Education and Research, 2025)
Micro dramas have quickly emerged as a ubiquitous cultural genre in the digital realm, but little is known regarding the diffusion of their usage socially and educationally in all-media communication space. This paper suggests a PageRank Complex Network Algorithm with a Graph Neural Network (PRCNA-GNN) to predict the adoption of cross-platform micro dramas based on multimodal data that consists of text, emoji, and static/dynamic memes. The fine-grained emotion and polarity analysis is supported by a custom set of Twitter posts exceeding one million posts annotated. PRCNA-GNN has better performance, as it can reach the accuracy of 93.7% precise 92.6% recall, and 92.9% F1-score. Adoption curves are close to actual trends of cumulative views and shares, and ablation experiments warrant the significance of PageRank weighting, multimodal characteristics and active learning. In addition to technical benefits, the results indicate the socio-cultural impact of micro dramas in the process of forming digital participation and possibly its educational importance in the development of multimodal literacy, narrative involvement, and creative learning.